Hubungan Kesiapan Fisik, Mental, dan Psikologis Anak dengan Keberhasilan Toilet Training pada Anak Usia 3-5 Tahun Di Posyandu Gading IV Palem Nirwana Desa Dukuh Tengah Sidoarjo - Sisilia Indriasari; Fiorent Eksa Juanita (Jurnal Keperawatan Muhammadiyah, 2022)
Before doing toilet training, parents need to identify signs of readiness that their child has. There are some children over 5 years old who still wet the bed and their parents just let the child go, even though it is the parent's job to teach toilet training. The purpose of this study was to identify the corellation  between physical, mental, and psychological readiness with the success of toilet training in children aged 3-5 years. This study used an analytic observational research design with a cross sectional approach. The sampling technique used is simple random sampling with a total of 34 respondents. The instrument used is a questionnaire. The results showed the relationship between physical and mental readiness of children and the success of toilet training -value = 0.001 = 0.05. Meanwhile, for the relationship between psychological readiness and the success of toilet training -value = 0.002 = 0.05. It means that there is a relationship between children's physical, mental and psychological readiness with the success of toilet training. Family support is needed in getting children to practice toilet training so they can do it independently.